SANG DAŚARATHA AS A ROLE MODEL OF THE HINDU’S IDEAL LEADERSHIP (Textual Analysis of Kakawin Rāmāyaṇa Sargah I Pada 3) - I Ketut Gunarta (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
The Kakawin Rāmāyaṇa itself is an Old Javanese literary work adapted from the Sanskrit epic Rāmāyaṇa by Valmiki. This work not only serves as entertainment but also as a source of moral and ethical teachings for the Old Javanese society. In the Kakawin Rāmāyaṇa, the character of Sang Daśaratha is described in depth, especially in Sargah (chapter) I Pada (stanza) 3. This research focuses on the effort to elaborate in detail the leadership patterns of Sang Daśaratha using a qualitative research method with a textual analysis approach. In the process, several results were obtained: a Hindu leader who applies the ideal leadership principles in Kakawin Rāmāyaṇa Sargah I Pada 3 must be oriented towards a typical leader who understands the concept of the Vedic teachings. This can be explored through fundamental principles that include dharma, sattva, karma, self-knowledge and awareness, vasudhaiva kutumbakam, integrity and ethical leadership, as well as interconnectedness and holistic vision. It is also important for a Hindu leader to always devote themselves to the Gods. In the principles shown in Kakawin Rāmāyaṇa Sargah I Pada 3, at least three deities are shown to be central entities that must be worshiped, namely Lord Brahma, Lord Vishnu, and Lord Shiva, as well as Lord Agni. In addition, a leader must also have a soul of love for their family and people and never forget their ancestors, because all of that is a source of strength and inspiration. Keyword: Kakawin Rāmāyaṇa, Leadership, Sang Daśaratha